Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Calculate the series \begin{equation} \sum_{n=0}^{\infty} \dfrac{1}{(4n+1)(4n+3)}. \end{equation}

share|improve this question
3  
What have you tried so far? –  Argon Jun 1 '12 at 21:11
7  
Eat your peas. (Seriously though, do make an effort to include your work and to ask a question rather than state a demand.) –  rschwieb Jun 1 '12 at 21:12
    
Hello Marcos. Do you know about accepting answers to your questions? –  Antonio Vargas Jun 1 '12 at 23:46

6 Answers 6

Hint:

$$\frac 1 {(4n+1)(4n+3)}=\frac 1 2\left(\frac{1}{4n+1}-\frac 1{4n+3}\right) $$

Then note that

$$\frac{1}{{4n + 3}} - \frac{1}{{4n + 1}} = \frac{1}{{2\left( {2n+1} \right) + 1}} - \frac{1}{{2\left( {2n} \right) + 1}}$$

from where

$$\sum\limits_{n = 1}^m {\left( {\frac{1}{{4n + 3}} - \frac{1}{{4n + 1}}} \right)} = 1 - \frac{1}{3} + \frac{1}{5} - \frac{1}{7} + - \cdots + \frac{1}{{2(2m + 1) + 1}} - \frac{1}{{2(2m) + 1}} $$

then recall the series for $\tan ^{-1}x$.

share|improve this answer
    
@Henry Done. ´´´ –  Pedro Tamaroff Jun 1 '12 at 21:38

Here is another take on this. It may not be the most simple, but I think some may find it interesting.

Let $\chi(n)$ be the unique nontrivial Dirichlet character modulo $4$, so that by using $\frac{1}{(4n+1)(4n+3)}=\frac{1}{2}\left(\frac{1}{4n+1}-\frac{1}{4n+3}\right)$ your series equals $$\frac{1}{2}\sum_{n=1}^\infty \frac{\chi(n)}{n}=\frac{1}{2}L(1,\chi).$$ Noting that $\chi(n)=\left(\frac{d}{n}\right)$ with $d=-4$, and that the quadratic form $x^2+y^2$ is the only class with discriminant $D=-4$, we see that by the class number formula $$L(1,\chi)=\frac{2\pi}{\omega(d)\sqrt{|d|}}=\frac{\pi}{4},$$ where $\omega(d)$ is the number of symmetries of the corresponding complex lattice. (In our case $\omega(d)=4$, because it is the Gaussian integers).

Thus the original series evaluates to $\frac{\pi}{8}$.

share|improve this answer
    
Agreed, very interesting! The $\equiv 1, 3 \bmod 4$ part of the statement suggested that something was up. –  Dylan Moreland Jun 2 '12 at 17:44

We let

$$f(z)=\dfrac{1}{(4z+1)(4z+3)}$$

There are two poles of $f(z)$. They are $4z_0+3=0 \implies z_0=-\frac{3}{4}$ and $4z_1+1=0 \implies z_1=-\frac{1}{4}$.

Residue calculus tells us that

$$\sum_{n=-\infty}^{\infty} \dfrac{1}{(4n+1)(4n+3)}=-(\text{sum of residues of }\pi\cot(\pi z)f(z))$$

We calculate the residues of the poles ($b_0$ and $b_1$ for $z_0$ and $z_1$ respectively):

$$b_0=\operatorname {Res}_{z=z_0}=\lim_{z \to z_0}\frac{(z-z_0)\pi\cot (\pi z)}{(4z+1)(4z+3)}$$

Using L'Hopital's rule we have

$$b_0=\lim_{z \to z_0} \frac{\pi\cot (\pi z)-(z-z_0)\pi^2 \csc^2 (\pi z)}{4((4z+1)+(4z+3))}=\frac {\pi \cot (-3\pi/4)}{4(4)}=-\frac{\pi}{8}$$

Similarly, we have

$$b_1=\lim_{z \to z_1} \frac{\pi\cot (\pi z)-(z-z_1)\pi^2 \csc^2 (\pi z)}{4((4z+1)+(4z+3))}=\frac {\pi \cot (-\pi/4)}{4(4)}=-\frac{\pi}{8}$$

So

$$ \sum_{n=-\infty}^{\infty} \dfrac{1}{(4n+1)(4n+3)}=-(-\frac{\pi}{8}-\frac{\pi}{8})=\frac{\pi}{4}\implies \sum_{n=0}^{\infty} \dfrac{1}{(4n+1)(4n+3)}=\frac{1}{2}\frac{\pi}{4}=\frac{\pi}{8} $$

QED

share|improve this answer

Once you splitted the initial fraction within the sum as below:

$$\frac 1 {(4n+1)(4n+3)}=\frac 1 2\left(\frac{1}{4n+1}-\frac 1{4n+3}\right) $$

then you may consider the following formula that is very helpful:

If $a+b+c+d=0$, $$\sum_{k=0}^\infty \left(\dfrac{a}{4k+1} + \dfrac{b}{4k+2}+\dfrac{c}{4k+3}+\dfrac{d}{4k+4}\right) = \dfrac{a-c}{8} \pi + \dfrac{a+c-2d}{4} \ln(2) $$

Replace the specific values you have and you're done. The limit is $\frac{\pi}{8}$.

The proof is complete.

share|improve this answer
    
I'm interested in the formula you used. Can you give a few words about where it comes from? Or perhaps a reference? –  ranousse Jun 2 '12 at 18:28
1  
@ranousse: you may want to see this math.stackexchange.com/questions/149120/… –  Chris's sis Jun 2 '12 at 19:02

$\frac{ \pi }{8}$ is what i get...

share|improve this answer
2  
Nice, perhaps you'd tell us about the "how". –  Gigili Jun 1 '12 at 21:20
2  
Please don't downvote the guy, give him a chance. –  Pedro Tamaroff Jun 1 '12 at 21:25
3  
Looking at the question and all of the effort shown by the OP in this thread, this appears to me to be a pretty appropriate answer. –  Jonas Meyer Jun 2 '12 at 6:00
1  
@Jonas: I really like that interpretation. GIGO in this case becomes WIWO (work in work out). I fully support this standard. –  mixedmath Jun 7 '12 at 0:57

Here is another method.

We have that $$\sum_{n=0}^{\infty} x^{4n} = \dfrac1{1-x^4}$$ Integrate the above from $x=0$ to $x=t < 1$, to get $$\sum_{n=0}^{\infty} \dfrac{t^{4n+1}}{4n+1} = \int_0^{t} \dfrac{dx}{1-x^4} = \dfrac12 \left( \int_0^{t} \dfrac{dx}{1+x^2} + \int_0^{t} \dfrac{dx}{1-x^2} \right)\\ = \dfrac12 \left( \arctan(t) + \dfrac12 \left( \int_0^t \dfrac{dx}{1+x} + \int_0^t \dfrac{dx}{1-x} \right)\right)\\ =\dfrac12 \left( \arctan(t) + \dfrac12 \left( \log(1+t) - \log(1-t)\right)\right)$$ Now multiply throughout by $t$ to get, $$\sum_{n=0}^{\infty} \dfrac{t^{4n+2}}{4n+1} =\dfrac12 \left( t\arctan(t) + \dfrac12 \left( t\log(1+t) - t\log(1-t)\right)\right)$$ Now integrate the above from $t=0$ to $1$. Note that $$\int_0^1 t\arctan(t) dt = \dfrac{\pi-2}{4}$$ $$\int_0^1 t\log(1+t) dt = \dfrac14$$ $$\int_0^1 t\log(1+t) dt = -\dfrac34$$ The above integrals can be evaluated with relative ease by integration by parts. Hence, we now get that $$\sum_{n=0}^{\infty} \dfrac1{(4n+1)(4n+3)} = \dfrac12 \left( \dfrac{\pi-2}{4} + \dfrac12 \left( \dfrac14 - \left( - \dfrac34\right)\right)\right) = \dfrac{\pi}8$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.